Amino acid requirements of Streptococcus mutans and other oral streptococci. - Terleckyj, B (1975)
The amino acid requirements of Streptococcus mutans strains AHT, OMZ-61, FA-1, BHT, GS-5, JC-2, Ingbritt, At6T, OMZ-176, 6715, Streptococcus salivarius HHT, Streptococcus sanguis OMZ-9, and strain 72x46 were determined in a chemically defined medium. When grown anaerobically in the presence of sodium carbonate (or bicarbonate for a few strains), few amino acids were required. All strains tested required cystine (or cystine) as a nutrient. Three strains (S. mutans OMZ-176, FA-1, and BHT) required glutamate (and/or glutamine). A third amino acid (lysine for S. mutans FA-1 and histidine for S. mutans OMZ-176) was required by two of the three strains which required glutamate. The amino acids mentioned above were required for all conditions of incubation (and inoculum) tested. The requirements for several other amino acids were conditional, that is, dependent on the incubation conditions and inoculum used. For example, when carbonate was not added, glutamate was required by S. mutans GS-5. Aerobic incubations, with carbonate or bicarbonate added, resluted in requirements for glutamate and leucine by several strains. With these incubation conditions, one strain required isoleucine (S. mutans FA-1), another valine (S. mutans AHT), and a third tyrosine (72x46). Aerobic incubations in the absence of carbonate or bicarbonate further increased the number of amino acids required by several strains. Furthermore, when stationary-phase cultures replaced exponentially growing cultures as an inoculum, several strains required additional amino acids, presumably for the initiation of growth.